Manufacturing of the carbon/phenol composite bipolar plates for PEMFC with continuous hot rolling process. (15th November 2015) - Kim, Minkook; Choe, Jaeheon; Lim, Jun Woo; Lee, Dai Gil
Abstract: The bipolar plate is a major component determining the cost, volume and performance of a PEMFC (Polymer Electrolyte Membrane Fuel Cell) stack. Carbon composite/epoxy has been considered to be a potential material for bipolar plates due to its good mechanical properties, electrical conductivity and corrosion resistance. However, the long curing time of the epoxy matrix under high pressure remains an obstacle for mass production. In this study, a continuous process using hot rolling for the mass production of carbon/phenol composite bipolar plates has been developed. To accelerate the curing reaction of the phenolic resin, a p -toluene sulfonic acid catalyst was used. The temperature, time and steps for continuous hot rolling process were optimized with cure monitoring using a dielectrometry method. The areal specific resistance (ASR) and mechanical properties of the carbon/phenol composite bipolar plate were measured with respect to the manufacturing process. The surface of the composite bipolar plates was coated with graphite to reduce the ASR. It was found that the composite bipolar plate produced by the optimized hot rolling process satisfied the Department of Energy (DOE) targets.